Alcohol use patterns and risk of incident cataract surgery: a large scale case–control study in Japan - Kota Fukai; Ryo Terauchi; Yuko Furuya; Kei Sano; Shoko Nakazawa; Noriko Kojimahara; Keika Hoshi; Tadashi Nakano; Akihiro Toyota; Masayuki Tatemichi (Scientific Reports, 2022)
Abstract To examine the risk of incident cataract surgery associated with alcohol use patterns among Japanese adults. This was a case–control study evaluating 14,861 patients with incident cataract surgery and 14,861 matched controls. Subjects admitted to any of the 34 hospitals in Japan and aged between 40 and 69 years were included. Drinking patterns (drinking frequency, daily average drinks, and total amount of lifetime drinking), smoking history, lifestyle-related comorbidities, and occupational factors were surveyed by trained interviewers. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using conditional logistic regression models. For drinking frequency, ORs in the 1–3 days/week and 4–7 days/week groups were 1.10 (95% CI 1.03–1.17) and 1.30 (1.21–1.40), respectively. For average drinks, ORs in > 0–2 drinks/day, > 2–4 drinks/day, and > 4 drinks/day were 1.13 (1.06–1.20), 1.23 (1.12–1.35), and 1.16 (1.03–1.31), respectively. Both men and women had an increased risk of incident cataract surgery with increased total lifetime drinking, with a significant increase in risk occurring at > 90 drink-years for men and > 40 drink-years for women. A positive dose–response relationship was observed between alcohol consumption and cataract. Restricted drinking may help to reduce the progression of cataracts.